LC–MS/MS analysis of metformin, saxagliptin and 5‐hydroxy saxagliptin in human plasma and its pharmacokinetic study with a fixed‐dose formulation in healthy Indian subjects - Shah, Priyanka A.; Shah, Jaivik V.; Sanyal, Mallika; Shrivastav, Pranav S. (Biomedical chromatography, 2017)
A specific and rapid liquid chromatography–tandem mass spectrometry method is proposed for the simultaneous determination of metformin (MET), saxagliptin (SAXA) and its active metabolite, 5‐hydroxy saxagliptin (5‐OH SAXA) in human plasma. Sample preparation was accomplished from 50 μL plasma sample by solid‐phase extraction using sodium dodecyl sulfate as an ion‐pair reagent. Reversed‐phase chromatographic resolution of analytes was possible within 3.5 min on ACE 5CN (150 × 4.6 mm, 5 μm) column using acetonitrile and10.0 mm ammonium formate buffer, pH 5.0 (80:20, v/v) as the mobile phase. Triple quadrupole mass spectrometric detection was performed using electrospray ionization in the positive ionization mode. The calibration curves showed good linearity (r2 ≥ 0.9992) over the established concentration range with limit of quantification of 1.50, 0.10 and 0.20 ng/mL for MET, SAXA and 5‐OH SAXA respectively. The extraction recoveries obtained from spiked plasma samples were highly consistent for MET (75.12–77.84%), SAXA (85.90–87.84%) and 5‐OH SAXA (80.32–82.69%) across quality controls. The validated method was successfully applied to a bioequivalence study with a fixed‐dose formulation consisting of 5 mg SAXA and 500 mg MET in 18 healthy subjects. The reproducibility of the assay was demonstrated by reanalysis of 87 incurred samples.